Pick up plan in the case of a shuttle racks warehouse – an optimization approach - Kansy, Dawid (Plan pobrań w przypadku magazynu typu shuttle – podejście optymalizacyjne, 2020)
The shuttle racks system is dedicated to storing fast-moving goods on homogeneous pallets, while ensuring high efficiency in the use of storage space. The radioshuttle system consist of shuttle channels and a remote controlled transfer trolley. The research problem considered scientifically is to develop the tools to plan collecting products from the location of shuttle racks that guarantee a minimum number of blockages. The linear programming model ensures that the goods are picked up from the shuttle location which minimizes the number of blockages or completely eliminates them. The main aim is to present a method and an algorithm of the shuttle racks system that will plan storage location before storing goods on the racks based on backorders. As a result, goods are located lengthwise in the shuttle tunnel according to the order in linear, discrete programming models. The work presents the model and verifies the basic characteristics of the problems analysed and the solution obtained
Informatyka Ekonomiczna = Business Informatics, 2020, Nr 1 (55), s. 38-59
Keywords: mixed-integer linear programming; optimization modeling; logistics; warehouse; shuttle racks; programowanie liniowe; modelowanie optymalizacyjne; logistyka; magazyn; regały przepływowe